Coagulação da água da represa Vargem das Flores visando tratamento por filtração direta - Eliane Prado Cunha Costa dos Santos (2004)
In this study a comparison of the performance of coagulants ferric chloride, aluminum sulfate, ferric sulfate, and aluminum hydrochloride, each separately or in combination with cationic polymers was carried out in order to evaluate the removal of color and turbidity from eutrophic water, through direct downflow filtration. The treatment study used the raw water from a source that feeds a treatment plant which treats about 1.000 L/s through downflow direct filtration, where coagulation is preceded by chlorination, without pH adjustment for coagulation, and aluminum sulfate is used as coagulant in higher dosages than what is usually recommended for direct filtration, which has contributed for the short duration of filter runs of about 16 hours. Jar filtration experiments, zeta potential measurement, phytoplankton counting, and pilot plant experiments were done to simulate the filter run duration of the treatment plant filters. The purpose of the study was to evaluate if pH adjustment for coagulation, the choice of coagulant and the use of cationic polymers would make it possible to lower coagulant dosage closer to levels recommended for direct downflow filtration. In view of the results of theexperiments, it can be concluded that all coagulants tested in either lab or pilot plant scale were able to produce filtered water in accordance with the Brazilian standard for drinking water, as did both aluminum sulfate 2 with acid and PACl 10,6% Al2O3, which were used in pilot plant experiments. There was no significant difference, on a level of significance of 5%, between coagulants tested in either jar filtration experiments or in pilot plant experiments as to results in removal of turbidity and color. Simulating the treatment plant filter run using thepilot plant, a 25 hour long filter run was obtained. This is longer than what currently takes place at the treatment plant, which suggests the filtering medium used at the treatment plant may not be adequate.